Teachers' and preservice teachers' implicit attitudes toward ethnic minority students and implicit expectations of their academic performance. (July 2022) - Costa, Sara; Pirchio, Sabine; Glock, Sabine
Abstract: During the last decade, the body of research investigating teachers' implicit attitudes toward different student groups, particularly toward ethnic minority groups, has been consistently increasing. The Implicit Association Test (IAT) is the main test that is used for this research purpose. However, what has been neglected so far is the investigation of implicit expectations about ethnic minority students in terms of their academic performance. Thus, the aim of the current study was to employ the Relational Responding Task (RRT) in the educational context as this test allowed us to assess stereotypical expectations in a more holistic way than other implicit measures would allow. We administered the IAT to assess implicit attitudes and the RRT to assess implicit expectations in a sample of teachers and preservice teachers in Italy. We also administered a questionnaire to assess explicit prejudice. For 93 teachers and preservice teachers who worked on all three measures, their implicit attitudes toward and their implicit expectations about ethnic minority students were negative, whereas their explicit prejudice was low. We did not find any correlations between the different measures. The findings are discussed in terms of the reasons for the zero correlations, and the usefulness of considering an implicit measure for teacher expectations in future research is highlighted. In this vein, we might obtain deeper insight into the role that teachers play in the disadvantages ethnic minority students experience in school.